In-hospital Pediatric Cardiac Arrest in Honduras. Issue 1 (January 2015) - Matamoros, Martha; Rodriguez, Roger; Callejas, Allison; Carranza, Douglas; Zeron, Hilda; Sánchez, Carlos; del Castillo, Jimena; López-Herce, Jesús
<x xml:space="preserve">Abstract</x> Objectives The objective of this study was to analyze the characteristic and the prognostic factors of in-hospital pediatric cardiac arrest (CA) in a public hospital Honduras. Methods A prospective observational study was performed on pediatric in-hospital CA as a part of a multicenter international study. One hundred forty-six children were studied. The primary end point was survival at hospital discharge. Univariate and multivariate logistic regression analyses were performed to assess the influence of each factor on mortality. Results Cardiac arrest occurred in the emergency department in 66.9%. Respiratory diseases and sepsis were predominant causes of CA. Return of spontaneous circulation was achieved in 60% of patients, and 22.6% survived to hospital discharge. The factors related with mortality were nonrespiratory cause of CA (odds ratio [OR], 2.55; P = 0.045), adrenaline administration (OR, 4.96; P = 0.008), and a duration of cardiopulmonary resuscitation more than 10 minutes (OR, 3.40; P = 0.012). Conclusions In-hospital CA in children in a developing country has low survival. Patients with nonrespiratory causes and those who need adrenaline administration and prolonged resuscitation had worse prognosis.